Transcriptome profiling and analysis of patients with esophageal squamous cell carcinoma from Kazakhstan - Sharip, Aigul; Rakhimova, Saule; Molkenov, Askhat; Ashenova, Ainur; Kozhamkulov, Ulan; Akhmetollayev, Ilyas; Zinovyev, Andrei; Zhukov, Yuri; Omarov, Marat; Tuleutaev, Mukhtar; Rakhmetova, Venera; Terwilliger, Joseph D.; et al. (Frontiers in Genetics, 2024)
Esophageal squamous cell carcinoma (ESCC) is the predominant histological subtype of esophageal cancer in Central Asia, characterized by low detection rates and often diagnosed at advanced stages. Understanding the population-specific patterns of ESCC is crucial for selection of specific treatments. This study aimed to unravel ESCC's genetic basis in Kazakhstani patients and identify potential biomarkers for early diagnosis and targeted therapies.Among the Kazakhstani patients studied, ESCC with moderate dysplasia emerged as the most prevalent subtype, highlighting the distinctive clinical profile of ESCC in this population. Our in-depth analysis revealed 42 significantly upregulated and two significantly downregulated KEGG pathways (p-value <0.05), shedding light on the molecular mechanisms driving ESCC pathogenesis. Of particular interest were the elevated immune-related pathways, such as viral protein interaction with cytokines, rheumatoid arthritis, and oxidative phosphorylation, suggesting a crucial role of the immune system in ESCC development. Conversely, the most significantly downregulated pathways were associated with tight junctions and adherens junctions, indicating a potential involvement in the extracellular matrix degradation, a process crucial in cancer invasion and metastasis.The pivotal DEGs were mapped onto a protein-protein interaction network, revealing four distinct modules of closely connected nodes. Each module had specific functions: "module 1" primarily related to translational elongation, "module 2" linked to histone function and activation of metalloproteinases, and "module 3" and "module 4" principally associated with mRNA regulation and chemokine activity respectively. This analysis illustrated the participation of these pathways in the development of esophageal cancer. High-throughput transcriptome sequencing analysis has been instrumental in identifying critical molecular pathways involved in esophageal carcinogenesis, providing a more comprehensive understanding of the disease's pathogenesis. Such insights hold the potential to significantly enhance early diagnosis and precision treatment strategies for ESCC.